Studying Dependence on Carbonated Beverages among Students and its Consequences - Normurodov, Hazratova Hulkar; qizi, Boyqobilova O‘raloy G‘ayrat (American Journal of Biology and Natural Sciences, 2025)
This scientific study examines the level of dependence on carbonated beverages among students and their negative effects on the human body. During the research, the composition of carbonated drinks, consumption habits, and their physiological consequences were analyzed. Special attention was given to their impact on bone strength, gastrointestinal function, the nervous system, and metabolism, based on scientific sources.